2020
DOI: 10.25259/jgoh_41_2020
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis and expression of salivary opiorphin in painful oral soft-tissue conditions: A descriptive study

Abstract: Objectives: Opiorphin is an enkephalinase inhibitor which suppresses pain by acting on the opioid system. The levels of opiorphin in plasma and saliva have shown to vary in patients with burning mouth syndrome. This descriptive study was designed to estimate the salivary levels of opiorphin among individuals with painful oral soft-tissue conditions. Materials and Methods: Unstimulated whole saliva was collected from 60 individuals (20 controls, 20 traumatic and inflammatory conditions, and 20 patients with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Nejad et al 6 (2020) study revealed that salivary opiorphin levels in the patients, who had painful oral soft tissue lesions including traumatic and inflammatory conditions, as well as, in patients with oral pre-malignant or malignant lesions, were higher than in healthy subjects; their study confirmed that the severity and type of pain could effect on opiorphin levels. Therefore, assessment of patients' salivary opiorphin could be an indicator of the severity of pain.…”
Section: Discussionmentioning
confidence: 88%
“…Nejad et al 6 (2020) study revealed that salivary opiorphin levels in the patients, who had painful oral soft tissue lesions including traumatic and inflammatory conditions, as well as, in patients with oral pre-malignant or malignant lesions, were higher than in healthy subjects; their study confirmed that the severity and type of pain could effect on opiorphin levels. Therefore, assessment of patients' salivary opiorphin could be an indicator of the severity of pain.…”
Section: Discussionmentioning
confidence: 88%
“…The proportion of women in the studies ranged from 40 31 to 90.4% 30 . Studies were conducted in Croatia 27 , 29 , France 30 , India 8 , 46 , Iraq 38 , and Turkey 31 , 34 . All studies were published in English.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts to diagnose and treat OFP would benefit from the development of biomarkers in the context of the various inflammatory, infectious, autoimmune, and premalignant/malignant conditions that can affect the orofacial region. Saliva offers numerous advantages as a source of biomarkers of orofacial (and other) abnormalities, including pain 8 10 . For example, saliva and its constituents have been under investigation for more than a century, and collecting saliva samples is non-invasive and convenient 11 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that opiorphin release occurred primarily as a pain control mechanism, although no additional stress biomarkers were measured [ 52 ]. Other studies indicate that opiorphin's level might correlate with the levels of oral pain and stress [ 14 , 53 56 ]. Recently a cohort study of 503 healthy schoolchildren where opiorphin levels were higher and correlated to prior stress exposure [ 49 ] suggested the use of opiorphin to evaluate stress-related changes in children [ 49 ].…”
Section: Discussionmentioning
confidence: 99%